2017
DOI: 10.1111/jfbc.12374
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a peptide from soybean with cancer cell proliferation inhibition

Abstract: A peptide from protein hydrolysate fraction obtained from a high oleic acid soybean line (N98‐4445A) that had shown significant activity against human cancer cell lines was identified and purified. Three peptides showing highest activity were identified by reverse phase HPLC in the 10–50 kDa fraction of the protein and purified using peptide specific affinity chromatography column. The three individual peptides were tested for anti‐proliferative activity against blood, colon and liver cancer cell lines using 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
(42 reference statements)
2
6
0
Order By: Relevance
“…In the current study, TdLTP4 signi cantly increased the levels of antiin ammatory cytokine IL-10. These results are in concordance with those of Rayaprolu et al (2017) who reported that IL-6 and TNF-α production was considerably increased in LPS-stimulated RAW 264.7 cells but signi cantly inhibited by Hazelnut protein-derived peptide LDAPGHR in a dose-dependent manner . Sangtanoo et al (2020) reported that Peanut worm (Sipunculus nudus Linn.)…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, TdLTP4 signi cantly increased the levels of antiin ammatory cytokine IL-10. These results are in concordance with those of Rayaprolu et al (2017) who reported that IL-6 and TNF-α production was considerably increased in LPS-stimulated RAW 264.7 cells but signi cantly inhibited by Hazelnut protein-derived peptide LDAPGHR in a dose-dependent manner . Sangtanoo et al (2020) reported that Peanut worm (Sipunculus nudus Linn.)…”
Section: Discussionsupporting
confidence: 92%
“…Then, the cells were treated with a medium containing DHA‐PC (0, 12.5, 25, 50, 100, and 200 μg/ml). After incubation for 24, 48, 72 or 96 hr, the cells were incubated with thiazolyl blue tetrazolium bromide (MTT) solution (0.5 mg/ml) and cell proliferation was assessed using the MTT assay, as described previously (Rayaprolu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of different concentrations of Cornus officinalis peptides on CEF cell proliferation were tested by MTT method [38]. Briefly, CEF cells in the logarithmic phase were inoculated into 96-well plates at 8 × 10 −3 density and 100 µL of different concentrations of Cornus officinalis peptides were added.…”
Section: Cell Proliferation Experimentsmentioning
confidence: 99%